Emlékbeszéd március 15-én - Szabó, Béla (Gerundium, 2018)
Official Speech, March 15, 2010. The festive speech, of which a footnoted-extended version can be read here, attempted to highlight how the previous five generations of the students of higher education in Debrecen had participated in the celebration of the bourgeois revolution of 1848. It was also important to underscore in this speech that for about a hundred years the student body of the College, then of the University, of Debrecen celebrated together with, indeed at the forefront of, the population of the city while for the past few decades the rituals of the local celebrations have diverged.